Next-generation sequencing identifies novel microRNAs in peripheral blood of lung cancer patients - Keller, Andreas; Backes, Christina; Leidinger, Petra; Kefer, Nathalie; Boisguérin, Valesca; Barbacioru, Catalin; Heilmeier, Britta; Matzas, Mark; Huwer, Hanno; Katus, Hugo; Stähler, Cord; Meder, Benjamin; et al. (Molecular BioSystems, 2011)
MicroRNAs (miRNAs) are increasingly envisaged as biomarkers for various tumor and non-tumor diseases. MiRNA biomarker identification is, as of now, mostly performed in a candidate approach, limiting discovery to annotated miRNAs and ignoring unknown ones with potential diagnostic value. Here, we applied high-throughput SOLiD transcriptome sequencing of miRNAs expressed in human peripheral blood of patients with lung cancer. We developed a bioinformatics pipeline to generate profiles of miRNA markers and to detect novel miRNAs with diagnostic information. Applying our approach, we detected 76 previously unknown miRNAs and 41 novel mature forms of known precursors. In addition, we identified 32 annotated and seven unknown miRNAs that were significantly altered in cancer patients. These results demonstrate that deep sequencing of small RNAs bears high potential to quantify miRNAs in peripheral blood and to identify previously unknown miRNAs serving as biomarker for lung cancer.
Gesehen am 28.07.2022